Late Bilinguals Share Syntax Unsparingly Between L1 and L2: Evidence From Crosslinguistically Similar and Different Constructions. Issue 1 (6th December 2017) - Hwang, Heeju; Shin, Jeong‐Ah; Hartsuiker, Robert J.
Abstract: Languages often use different constructions to convey the same meaning. For example, the meaning of a causative construction in English ( Jen had her computer fixed ) is conveyed using an active structure in Korean ( Jen‐NOM her computer‐ACC fixed ), and yet little is known about how bilinguals represent and process such constructions. The present study investigated whether late bilinguals develop shared or language‐specific representations for crosslinguistically different (causatives) and similar (transitives) constructions. Using between‐language structural priming, Experiment 1 showed that proficient Korean‐English bilinguals exhibited a stronger priming effect for transitives than did less proficient bilinguals. Using a picture–sentence verification task, Experiment 2 showed that proficient bilinguals were more likely to apply the rules of Korean causatives to the processing of English causatives than were less proficient bilinguals. Our results suggest that Korean‐English bilinguals share syntactic representations for both similar and different constructions, indicating that the bilingual system is highly integrated.